When Can Management Science Research Be Generalized Internationally? - Rosenzweig, Philip M. (Management Science, 1994)
Discussion about international generalizability has rarely addressed the full scope of management science research. This paper identifies a number of obstacles to international generalizability, and shows how they affect technical systems research and social systems research in different ways. Examples of management science research are examined critically for their validity elsewhere in the world. Implications are discussed for the interpretation of existing research and for the design of research.